Osebnostne značilnosti in prisotnost socialne podpore samomorilno ogroženih posameznikov - Krajnc, Sebastijan (Medicinski razgledi, 2022)
Backgrounds. Higher risks of suicide have been observed in individuals who scored high on neuroticism traits on the Big Five personality model, and lower risks in those who scored high in the conscientiousness, extraversion and agreeableness traits. Openness has been positively correlated with suicidal ideations but negatively with carried out suicide attempts. Studies have thus far consistently implicated the protective role of social support in preventing suicidal ideation and suicide attempts. Methods. Clinical inter- views and self-reported questionnaires were administered to a sample of 24 (n = 24; 12 male, 12 female; age 20–60 years) patients with increased suicide risk who were hospitalized. Each patient was interviewed twice, on admission and before discharge. Data was obtai- ned by means of a semi-structured interview, demographics questionnaire, the Big Five Questionnaire, Social Support Questionnaire, Symptom Checklist-90-Revised question- naire, and suicide risk was determined with the Modified SAD PERSONS Scale. Statistical significance was determined using the t-test for dependent samples and Spearman’s rank correlation coefficient (?). Results. We have found a positive and statistically significant correlation between high trait neuroticism and suicidality (? = –0.471, p < 0.05). Perceived rate of satisfaction with social support was statistically significantly correlated with lower suicidality before discharge (p < 0.05). Discussion. We have confirmed our hypothesis that neuroticism will be positively correlated with suicidal behaviour, and partially confirmed the hypothesis that strong social support will be negatively correlated with suicidality, presenting a protective factor in preventing suicide risk.
Keywords: čustvena stabilnost; osebnostne značilnosti; samomori; samomorilno vedenje